Functional MRI and neural responses in a rat model of Alzheimer’s disease - Sanganahalli, Basavaraju G. (2013)
Based on the hypothesis that brain plaques and tangles can affect cortical functions in Alzheimer's disease (AD) and thus modify functional activity, we investigated functional responses in an AD rat model (called the Samaritan Alzheimer’s rat achieved by ventricular infusion of amyloid peptide) and age-matched healthy control. High-field functional magnetic resonance imaging (fMRI) and extracellular neural activity measurements were applied to characterize sensory-evoked responses. Electrical stimulation of the forepaw led to BOLD and neural responses in the contralateral somatosensory cortex and thalamus. In AD brain we noted much smaller BOLD activation patterns in the somatosensory cortex (i.e., about 50% less activated voxels compared to normal brain). While magnitudes of BOLD and neural responses in the cerebral cortex were markedly attenuated in AD rats compared to normal rats (by about 50%), the dynamic coupling between the BOLD and neural responses in the cerebral cortex, as assessed by transfer function analysis, remained unaltered between the groups. However thalamic BOLD and neural responses were unaltered in AD brain compared to controls. Thus cortical responses in the AD model were indeed diminished compared to controls, but the thalamic responses in the AD and control rats were quite similar. Therefore these results suggest that Alzheimer’s disease may affect cortical function more than subcortical function, which may have implications for interpreting altered human brain functional responses in fMRI studies of Alzheimer’s disease.